2017
DOI: 10.1177/0265407517705737
|View full text |Cite
|
Sign up to set email alerts
|

“Gay capital” in gay student friendship networks

Abstract: This article draws on qualitative interviews with 40 gay male undergraduates at four universities across England to explore the dynamics of participants’ friendship networks in the context of decreased homophobia. Describing their schools and universities as gay-friendly spaces, most participants developed close friendships with both straight and sexual minority peers in spontaneous ways, away from institutional venues such as lesbian, gay, bisexual, and transgender student societies. Building on Bourdieu’s co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 58 publications
0
12
0
1
Order By: Relevance
“…We are not sure why this is the case, but potential factors might include slight wording differences between the measures of gender typicality used in our study and in Egan and Perry's (2001) study. Additionally, our data were gathered 15 years after the publication of Egan and Perry's study; much has changed regarding the visibility and acceptance of gender diversity since then (Becker et al 2017;Morris 2018;Yu et al 2017).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…We are not sure why this is the case, but potential factors might include slight wording differences between the measures of gender typicality used in our study and in Egan and Perry's (2001) study. Additionally, our data were gathered 15 years after the publication of Egan and Perry's study; much has changed regarding the visibility and acceptance of gender diversity since then (Becker et al 2017;Morris 2018;Yu et al 2017).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…As a result, some young gay men may be more comfortable with overtly resisting the hegemonic masculinity discourse, notwithstanding their acknowledgement of its dominance (Morris, 2017;Wilson et al, 2010). Further, and as one participant in this study stated explicitly, embodying a feminized identity may facilitate expressions of defiance against normative cultural expectations of men -an opportunity to "own" and show pride in gayness.…”
Section: Discussionmentioning
confidence: 77%
“…It has also been suggested that being gay is increasingly celebrated by young heterosexual people rather than denigrated, and that young gay men can enjoy promoted positions in their peer groups, because gay identities carry social prestige (Morris, 2017). As a result, some young gay men may be more comfortable with overtly resisting the hegemonic masculinity discourse, notwithstanding their acknowledgement of its dominance (Morris, 2017;Wilson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social support from peers was identified as a protective factor in the lives of LGBTI+ youth ( n = 32). A range of peer relationships were identified: close friendships with gender and sexual minority peers [ 52 , 53 , 55 , 61 , 62 , 68 , 69 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ], including romantic relationships [ 53 , 90 , 96 , 97 , 98 , 99 ], cross-sexual orientation friendships [ 52 , 55 , 100 , 101 , 102 ] and supportive peer relationships [ 52 , 53 , 57 , 61 , 65 , 69 , 72 , 75 , 88 , 90 , 93 , 94 , 95 , 102 ]. Such relationships with peers were regarded as mutually beneficial and reciprocal and of increasing importance as young people became older [ 72 , 77 , 88 , 92 ].…”
Section: Resultsmentioning
confidence: 99%